Only a minority of thrombectomy candidates are admitted during night shift: a rationale for diurnal stroke care planning - Reuter, Björn; Stock, Christian; Ungerer, Matthias; Hyrenbach, Sonja; Bruder, Ingo; Ringleb, Peter A.; Kern, Rolf; Gumbinger, Christoph (Frontiers in neurology, 2020)
Background: Widespread quick access to mechanical thrombectomy (MT) for acute ischemic stroke (AIS) is one of the main challenges in stroke care. It is unclear if newly established MT units are required 24h/7d. We explored the diurnal admission rate of patients with AIS potentially eligible for MT to provide a basis for discussion of daytime-adapted stroke care concepts. Methods: Data collected from the Baden-Württemberg Stroke Registry were assessed (2008-2012). We analysed the admission rate of patients with AIS stratified by the National Institutes of Health Stroke Scale (NIHSS) score at admission in 3-h intervals. An NIHSS score ≥10 was considered a predictor of large vessel occlusion. The average annual admission number of patients with severe AIS were stratified by stroke service level and calculated for a three-shift model and working/non-working hours. Results: Of 91,864, 22,527 (21%) presented with an NIHSS score ≥10. The average admission rates per year for a hospital without Stroke Unit (SU), with a local SU, with a regional SU and a stroke centre were 8, 52, 90 and 178, respectively. Approximately 61% were admitted during working hours, 54% in the early shift, 36% in the late shift and 10% in the night shift. Conclusions: A two-shift model, excluding the night shift, would cover 90% of the patients with severe AIS. A model with coverage during working hours would miss approximately 40% of the patients with severe AIS. To achieve a quick and area-wide MT, it seems preferable for newly implemented MT-units to offer MT in a two-shift model at a minimum.
Gesehen am 05.11.2020